Logika Mistika Tan Malaka dalam Perspektif Al-Qur’an (Kajian Tafsir Tentang Relasi Akal dan Keimanan) - Farros Iqbal (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This article explores mystical logic, a term introduced through the critique of Tan Malaka's thought in Indonesia, in the context of Qur'anic interpretation, particularly the relationship between reason and faith. Using a thematic exegetical approach, this article unpacks the structure of Qur'anic faith, which integrates reason ('aql) and inner experience (qalb/yaqin), and compares it with the phenomenon of mystical logic that remains strong in Indonesian society. Case studies demonstrate how popular understandings of mysticism often deviate from the Qur'anic principles of monotheism and rationality. The analysis draws on key exegetical works such as the Tafsir al-Mishbah (Quraish Shihab), the Tafsir of Ibn Kathir, and contemporary Sufism. The results show that the Qur'an does not reject inner experience, but rather synthesizes reason and mysticism within a rational and ethical framework of revelation. Keywords: Mystical Logic, Qur'an, Interpretation, Reason, Faith